Estimation, Control and Verification Procedures for a Reliability Model Based on Variables Data - Ehrenfeld, Sylvain; DeCicco, Henry (Management Science, 1964)
A technique is discussed for framing a reliability model in terms of variables data rather than attribute data. A particular model is developed in terms of a Gamma process; it is believed that such a model may prove applicable to items undergoing long term storage, especially where continuous observations are not feasible. Estimates of the parameters of the model, along with a discussion of prodcedures for control and verification are included.